The Road to Sustained Growth in Jamaica - World Bank (Washington, DC, 2013)
Jamaica's economic history is one of paradoxes, and potential - it has an English-speaking, and reasonably well-educated labor force, is close to the world's largest market, the United States, and, has an abundance of natural beauty, which has spurred tourism - and, many of its social, and governance indicators are strong, including near universal school enrollment. Poverty rates are below that of comparable countries. Yet, the Jamaican story is marked by the paradoxes of low growth in GDP and high employment, despite high investment, and important achievements in poverty reduction. This paper attempts to explain these paradoxes, and concludes that one possible explanation is that GDP has been understated. Amid these challenges, this report proposes that a "bandwagon" approach to reforms may be needed to improve prospects for sustained growth, with policy actions on several fronts, including measures to avert crisis, while continuing to strengthen social safety nets, as well as short- and long-term policies, such as reducing the growth of public expenditure, and tackling crime. Given that policy choices are likely to be difficult, it argues that an approach based on social dialogue, and consensus building is essential to create ownership for future reforms among all stakeholders.